2004
DOI: 10.1002/bies.20107
|View full text |Cite
|
Sign up to set email alerts
|

Hop: more than an Hsp70/Hsp90 adaptor protein

Abstract: Molecular chaperones facilitate the correct folding of other proteins under physiological and stress conditions. Recently it has become evident that various co-chaperone proteins regulate the cellular functions of these chaperones, particularly Hsp70 and Hsp90. Hop is one of the most extensively studied co-chaperones that is able to directly associate with both Hsp70 and Hsp90. The current dogma proposes that Hop functions primarily as an adaptor that directs Hsp90 to Hsp70-client protein complexes in the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
150
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(156 citation statements)
references
References 83 publications
(108 reference statements)
3
150
0
1
Order By: Relevance
“…4 D). Hsp70 and -90 have been shown to interact (Carrello et al, 2004;Odunuga et al, 2004;Reyes-Del Valle et al, 2005), and we believe that the apparent increased amount of Hsp90 is a result of a dissociation of the Hsp70/90 complex during the ion exchange process, resulting in either increased antigenicity or increased free Hsp90. Interestingly, although addition of recombinant Hsp90 to motoneuron cultures did promote survival, it does not appear to be able to contribute to survival in MEx when Hsp70 is removed (Fig.…”
Section: Caspase-3 Activation Is Reduced When Motoneurons Are Treatedmentioning
confidence: 69%
“…4 D). Hsp70 and -90 have been shown to interact (Carrello et al, 2004;Odunuga et al, 2004;Reyes-Del Valle et al, 2005), and we believe that the apparent increased amount of Hsp90 is a result of a dissociation of the Hsp70/90 complex during the ion exchange process, resulting in either increased antigenicity or increased free Hsp90. Interestingly, although addition of recombinant Hsp90 to motoneuron cultures did promote survival, it does not appear to be able to contribute to survival in MEx when Hsp70 is removed (Fig.…”
Section: Caspase-3 Activation Is Reduced When Motoneurons Are Treatedmentioning
confidence: 69%
“…In addition, Hop is involved in cell-cycle regulation and steroid receptor maturation (24,34,35), and it is homologous to the CHIP complex, of importance to CFTR degradation (36). Hop has a conserved cysteine (C403) (23,24) located in an S-nitrosylation motif believed to be relevant to S-nitrosylation (26). We found that GSNO inhibited Hop expression in all cell lines.…”
Section: Discussionmentioning
confidence: 86%
“…These include Hsp90 itself, protein von Hippel Lindau, S100A class proteins, and others (37)(38)(39)(40). Hop is believed to have an array of important cellular functions that could be affected by GSNO (23,24), an important consideration with regard to potential toxicities of S-nitrosothiol therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Two members of the HSP90 family was also upregulated (HSP90AB1, HSP90AA1) and so was cofactor AHSA1 which interacts with HSP90AA1 as an activator, while the HSP90s assists in protein folding and protein stabilization (Panaretou et al 2002). STIP1, a member of HSP70-HSP90 organizing protein (HOP) family which functions as a cochaperone that reversibly links together HSP70 and HSP90 protein chaperones (Odunuga et al 2004) and prostaglandin E synthase 3 (PTGES3) which functions as a cochaperone, along with HSP90 were also upregulated. HS results in an increase in cytotoxic protein in the endoplasmic reticulum (ER), HERPUD1 which was found to be upregulated in this study functions in processing and degradation of these cytotoxic protein by participating in ER-associated degradation (ERAD) (Nogalska et al 2006).…”
Section: Heat Stress Resulted In the Activation Of Heat Shock Factorsmentioning
confidence: 99%